The Evolving Role of Pharmacy Professionals in Modern Healthcare Systems - Elaf Jameel Felemban, Mohammed Musaad Almasoudi, Naif Abdulrahman Alzaidi, Husain Essa Haij,‏ Hisham Adil M Alsuqati, Abeer Sulaiman Alkhammash,‏ Manar Abdulmohsen Zahrallayali, Mohammed Abdulmohsin Alhazmi (Journal of International Crisis and Risk Communication Research, 2024)
Introduction: Amid changing healthcare environments in contemporary practice contexts, pharmacy personnel has become one of the essential actors in providing care to patients as well as population health. Once merely responsible for dispensing prescribed medications and guaranteeing the correct preparation of such, contemporary pharmacists remain active within a different, more incorporated, healhtcare structure. Such a transformation is rooted in enhancement in medical practice and the continued evolution of the health care unit in delivery of services in which the input of the professionals in the field of pharmacy is important in handling various health issues. Aim of work: To explore the evolving role of pharmacy professionals within modern healthcare systems, examining the factors driving their expanded scope of practice, the new responsibilities they undertake, and their impact on patient outcomes and healthcare efficiency. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Evolving, Role, Pharmacy, Professionals, Modern, Healthcare Systems. The search was restricted to publications from 2016 to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: The evolving role of pharmacy professionals suggests a constant adaptation of healthcare systems to address new challenges and seize the opportunities that present themselves. Going from clinical practice to public health, research, and leadership, pharmacists have emerged as valuable actors in patient care and the development of healthcare. Pharmacy professionals are therefore poised to advance health outcomes, address disparities, and increase the effectiveness of the healthcare system as they practice is extended across a broader continuum. Nonetheless, they need to be encouraged, funded, and appreciated, so that they can achieve their potential to the fullest. With such shifts incorporated, the enhanced pharmacy will persist to be a cornerstone of the ever-evolving healthcare delivery system to the eventual benefit of the global populace.